Adherence to healthy lifestyle behaviors as a preventable risk factor for severe hypoglycemia in people with type 2 diabetes: A longitudinal nationwide cohort study. Issue 9 (24th May 2022) - Yun, Jae‐Seung; Han, Kyungdo; Park, Yong‐Moon; Han, Eugene; Lee, Yong‐ho; Ko, Seung‐Hyun
Abstract: Aims/Introduction: We investigated the associations between a combination of lifestyle factors and changes to these factors and the subsequent risk of severe hypoglycemia (SH) in type 2 diabetes patients. Materials and Methods: Individuals with adult type 2 diabetes who underwent consecutive 2‐year interval health screening programs from 2009 to 2012 from the Korean National Health Insurance Service database were included and followed up until 2018. Information on history of smoking status, alcohol consumption and physical activity, as well as changes to these factors, was obtained. The primary outcome was incident SH. Results: Of the 1, 490, 233 type 2 diabetes patients, 30, 539 (2.1%) patients developed SH. Current smokers and heavy drinkers had increased risk of SH, compared with non‐smokers and non‐drinkers, respectively (hazard ratio 1.28, 95% confidence interval 1.23–1.34; hazard ratio 1.22, 95% confidence interval 1.15–1.30). However, regular physical activity was associated with reduced SH risk (hazard ratio 0.79, 95% confidence interval 0.77–0.82). A combination of unhealthy lifestyle habits was associated with increased SH risk in a dose‐dependent fashion ( P for trend <0.001). Compared with participants without changes in their unhealthy lifestyles, participants who improved lifestyles had decreased risk of SH. Conclusions: Greater adherence to healthy lifestyle factors and any improvement in unhealthy lifestyle habits were associated with a substantially lower risk of SH in individuals with type 2 diabetes. Abstract : Unhealthy lifestyle habits are associated with an increased risk of severe hypoglycemia in type 2 diabetes patients. If people with type 2 diabetes improve their unhealthy lifestyles, they can reduce the risk of severe hypoglycemia. Similar to the 'legacy effect' of intensive glycemic control for the prevention of diabetic complications, adherence to healthy lifestyle habits or discontinuation of unhealthy lifestyle factors can reduce the risk of severe hypoglycemia in type 2 diabetes patients.